Family support for young Ḥāfiẓ Al-Qur’ān - Muthmainah; Abur Hamdi Usman (Journal of Early Childhood Care and Education (JECCE), 2022)
No children can develop without the support of the family. Family support is one of the contributing factors to children's success. This study aims to illustrate family support for young Ḥāfiẓ al-Qur’ān . This research is descriptive qualitative research. The research subjects are five children, Ḥāfiẓ al-Qur’ān since they were seven years old, their teachers, and their parents. Data collection was done through interviews and observation, followed by an analysis using the interactive model by Miles, Huberman, and Saldana. The research findings show that family support for young Ḥāfiẓ al-Qur’ān includes emotional support, appreciation, instrumental support, information, and spiritual support. Future studies should focus on the parents' spiritual support for children's success, as it requires more theoretical studies. This research is expected to inspire and motivate parents to accompany their children, especially in memorizing the Qur'an.